A Comparative Study of the First and Second Waves of the COVID-19 Pandemic Response in Thailand - จูฑะรงค์, วัชราภรณ์; จาง, เหวยเหวิน; เกิดวิบูลย์, จิณณวัตร (Journal of Health Science of Thailand, 2022)
This research studied the role of the Thai government in addressing a public health emergency using prevention and control measures for COVID-19, and provided an analysis of the results of using these measures. The methods include: (1) recording and monitoring the number of COVID-19 confirmed cases, recovered cases, and fatalities in Thailand from 1 January 2020, to 2 April 2021, from data obtained from the Center for COVID-19 Situation Administration (CCSA); (2) study on prevention and control measures for COVID-19 as set out in the regulations No.1 to No.18; and (3) comparison of the first and second waves of COVID-19 pandemic response. The results found that Thailand started to apply the outbreak response measures early. During the first wave of the COVID-19 pandemic response, Thailand implemented strict lockdown measures, which were ordered to become effective in all areas of the country. With appropriate approaches to the situation, Thailand could control the COVID-19 pandemic effectively at the first wave response. Cumulative confirmed cases in the first wave of the COVID-19 pandemic were less than that of the second wave. During the second wave, Thailand put focus on the balance between disease control and economic recovery, which highlighted the use of COVID-19 zoning areas together with integrated control measures. In addition, the Thai Government began to distribute vaccines to the public. The total number of deaths was less than in the first wave; and there were more recovered cases. In summary, Thailand’s response to the COVID-19 pandemic using specific prevention and control measures for COVID-19 was appropriate for the situation in each period. Thailand could reduce and control new confirmed cases per day in the first wave, and could reduce death cases and increase total recovered cases in the second wave.